2021
DOI: 10.3390/genes12121877
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Sepsis in Platelets Using MicroRNAs and Membrane Antigens

Abstract: The present study proposes to legitimize in sepsis a characteristic found in platelets that suffer storage lesions in blood banks, which is the increased expression of miRNA miR-320a in relation to miR-127. Under physiologically normal conditions, an inverse relationship is observed. The aim of this study was to verify whether the analysis of miR-320a and miR-127 expression in platelets could detect a decrease in their viability and function due to the presence of pathogens in the blood of patients hospitalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Thrombocytopenia is associated with a higher mortality rate in sepsis patients [ 20 ] . Research by Vieira Corrêa PCM [ 29 ] and others has confirmed a significant correlation between low platelet counts and the severity and mortality rate of sepsis, and persistent thrombocytopenia is considered an independent risk factor for sepsis-related death. [ 19 ] The present study also shows that the platelet count of the non-survivors was lower than that of the survivors (156.99 ± 86.46 vs 267.34 ± 102.22, t = 8.539, P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia is associated with a higher mortality rate in sepsis patients [ 20 ] . Research by Vieira Corrêa PCM [ 29 ] and others has confirmed a significant correlation between low platelet counts and the severity and mortality rate of sepsis, and persistent thrombocytopenia is considered an independent risk factor for sepsis-related death. [ 19 ] The present study also shows that the platelet count of the non-survivors was lower than that of the survivors (156.99 ± 86.46 vs 267.34 ± 102.22, t = 8.539, P < .001).…”
Section: Discussionmentioning
confidence: 99%